Contemporary Issues of Islamic Family Law: The Waithood Phenomenon and the Impact of the Sex Recession in Indonesia in Review of Sadd al-dzari'ah - Muhammad Hafis; Elmiati, Nia; Syafitri, Juliani (Legitima : Jurnal Hukum Keluarga Islam, 2024)
Purpose – This research aims to examine the phenomena of waithood (delaying marriage) and sex recession as contemporary issues in Islamic family law in Indonesia. Both phenomena demonstrate complex social dynamics, which not only affect family structures but also have far-reaching impacts on social, cultural, religious and educational dimensions. Using the sadd al-dzari'ah approach, this research seeks to identify the root of the problem and offer solutions that are in accordance with the principles of Islamic family law. Methods - The research method used is juridical-normative with a philosophical and conceptual approach. The collection of legal materials uses document studies with prescriptive analysis techniques based on logic and deductive legal reasoning. The theory used is sadd al-dzari'ah. This theory was chosen because it is suitable to see the existing phenomenon. Sadd al-dzari'ah is a theory in Islamic law that prevents, prohibits, or closes the way of an act that is initially permitted but can cause damage. Findings - Based on this research, it can be concluded that Waithood is influenced by various factors, ranging from mental readiness, the feminism movement, social conditions, and the development of modernity to economic factors that are the impact of the contemporary era. Waithood has far-reaching potential impacts, including declining birth rates, demographic imbalances, and sex recessions. Sadd al-dzari'ah theory can be applied to prevent the negative impacts of Waithood and sex recession. Research implications - This study is expected to provide a new perspective in understanding the contemporary challenges faced by the younger generation and their implications for the sustainability of society and the state.